Pemerintahan Raja Salomo: Keberhasilan dan Tantangan dalam Masa Kepemimpinannya - Saul Napat; Obertina Gomor; Yohana Katerina Tinopi; Sarmauli Sarmauli (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research examines the journey and leadership transformation of King Solomon, who was initially known as the wisest leader in history, but later became a despotic leader. This research analyzes the role of theology in the narrative of the Story of King Solomon, focusing on aspects of pride and prosperity that contributed to the root of Solomon's downfall. In this context, this research explains how Solomon's initial wisdom was replaced by luxury and the negative influence of wealth, so that he fell into various sins against his people and God. And all the mistakes he made were related to changes in the leadership paradigm. The results of this research provide insight into the importance of morality and spiritual values ​​in maintaining leadership quality, as well as illustrating how the fall of a leader can be a valuable lesson in a theological context.